4-Methylumbelliferone Suppresses Hyaluronan Synthesis and Tumor Progression in SCID Mice Intra-abdominally Inoculated With Pancreatic Cancer Cells. Issue 2 (February 2017) - Nagase, Hayato; Kudo, Daisuke; Suto, Akiko; Yoshida, Eri; Suto, Shinichiro; Negishi, Mika; Kakizaki, Ikuko; Hakamada, Kenichi
Abstract : Objectives: Pancreatic ductal adenocarcinoma contains large amounts of the glycosaminoglycan hyaluronan (HA), which is involved in various physiological processes. Here, we aimed to clarify the anticancer mechanisms of 4-methylumbelliferone (MU), a well-known HA synthesis inhibitor. Methods: MIA PaCa-2 human pancreatic cancer cells were used. We evaluated cellular proliferation, migration, and invasion in the presence of MU, exogenous HA, and an anti-CD44 antibody. We also analyzed apoptosis, CD44 expression, and HA-binding ability using flow cytometry. The HA content in tumor tissue was quantified and histopathologically investigated in mice who had been inoculated with cancer cells. Results: In vitro, MU inhibited pericellular HA matrix formation; however, HAS3 mRNA was up-regulated. Treatment with 0.5 mM MU suppressed cellular proliferation by 26.4%, migration by 14.7%, and invasion by 22.7%. Moreover, MU also significantly increased apoptosis. CD44 expression and HA-binding ability were not altered by MU. In vivo, MU suppressed HA accumulation in pancreatic tumors and improved survival times in tumor-bearing mice. Conclusions: 4-Methylumbelliferone indirectly caused apoptosis in pancreatic cancer cells by inhibiting HA production. 4-Methylumbelliferone may be a promising agent in the treatment of pancreatic cancer.